2003
DOI: 10.1029/2003gl017536
|View full text |Cite
|
Sign up to set email alerts
|

Air‐sea interaction at an oceanic front: Implications for frontogenesis and primary production

Abstract: [1] Based on recent satellite observations, we hypothesize that there exists a significant air-sea interaction at the shelfbreak front in the East China Sea. An idealized oceanatmosphere coupled model was designed to test this hypothesis and to study the physical processes involved in such an interaction, with emphasis on the oceanic part. A positive feedback between ocean and atmosphere was identified in the model and its consequences were evaluated. We found that air-sea interaction, when combined with slopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…The impacts of typhoons on the ocean are investigated using both observations (D'Asaro, 2003;Han et al, 2012;Price, 1981;Stramma, Cornillon, & Price, 1986;Sun et al, 2010;Wang & Zhao, 2008) and model simulations (Chang, 1985;Chen, Liu, Tang, & Wang, 2003;Emanuel, 1999;Liu, Wang, & Huang, 2008;Price, Sanford, & Forristall, 1994;Tsai, Chern, & Wang, 2008). From satellite imagery, it has been determined that the maximum surface cooling occurs before the passage of the eye of the typhoon (D'Asaro, 2003), or a few days after the passage of the eye (Stramma et al, 1986;Subrahmanyam et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of typhoons on the ocean are investigated using both observations (D'Asaro, 2003;Han et al, 2012;Price, 1981;Stramma, Cornillon, & Price, 1986;Sun et al, 2010;Wang & Zhao, 2008) and model simulations (Chang, 1985;Chen, Liu, Tang, & Wang, 2003;Emanuel, 1999;Liu, Wang, & Huang, 2008;Price, Sanford, & Forristall, 1994;Tsai, Chern, & Wang, 2008). From satellite imagery, it has been determined that the maximum surface cooling occurs before the passage of the eye of the typhoon (D'Asaro, 2003), or a few days after the passage of the eye (Stramma et al, 1986;Subrahmanyam et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Spall (2007) has shown that the feedback from winds blowing across SST fronts modifies the growth rate and wavelength of baroclinically unstable waves. Chen et al (2003) coupled the Lindzen and Nigam (1987) model with an oceanic model to study shelf-break frontogenesis and showed a positive feedback that locally strengthened both the wind and the front. Perlin et al (2007) found that the SST in a coastal upwelling regime was lower near the coast after several days using a coupled atmosphere-ocean mesoscale model.…”
Section: Introductionmentioning
confidence: 99%
“…Such frontal-scale wind curl is neither resolved in other wind stress products nor in global GCMs, but may contribute to the recirculation of the Gulf Stream by Sverdrup dynamics (Behringer et al 1979). Chen et al (2003) suggest that the interaction between the SST front and the wind curls is an important element of ocean-front dynamics that strongly affects vertical nutrient transport and bioproductivity.…”
mentioning
confidence: 99%